Exercise templates with Sage Math - Cruz, João Pedro Antunes Ferreira da (2012)
Students can benefit from the study of a detailed answer of an exercise after trying to solve it in traditional pen-and-paper way as has been verified in literature. This basic fact was the incentive to the creation of a new package, for the growing community of users of Sage Math, that allows an author to add, change and delete parameterized exercise templates, with detailed answer, from one or more personal databases, as well as producing new exercises in a booklet style or exam form.